ANALISIS KELAYAKAN INVESTASI PROYEK COAL BOILER PT. XYZ - Chandra Tjong (Business Management Journal, 2017)
Since the happening of increase of oil price in August 2005, PT. XYZ starts to think over to use the source of other alternative energy specially to replace HTM burner and steam boiler which still use IDO and diesel fuel. Source of alternative energy is coal because the source of coal in Indonesia is in a large amount. Because of that PT. XYZ plans to change HTM burner and steam boiler with coal boiler. Analysis eligibility of investment of coal boiler is needed to evaluate from technical aspect and monetery asect which assign value and time return of most optimal investment. The method that use for that analysis are payback period, net present value, profitability index and internal rate of return in three condition that is pessimist condition, normal condition and optimism condition. Besides also analyze influence of project investment to production cost at that condition. Investment of coal boiler project is suitable. Keywords : Production cost, payback period, net present value, index profitability, internal rate of return.